2018
DOI: 10.1016/j.bone.2018.09.008
|View full text |Cite
|
Sign up to set email alerts
|

Demethylation of ITGAV accelerates osteogenic differentiation in a blast-induced heterotopic ossification in vitro cell culture model

Abstract: Trauma-induced heterotopic ossification is an intriguing phenomenon involving the inappropriate ossification of soft tissues within the body such as the muscle and ligaments. This inappropriate formation of bone is highly prevalent in those affected by blast injuries. Here, we developed a simplified cell culture model to evaluate the molecular events involved in heterotopic ossification onset that arise from the shock wave component of the disease. We exposed three subtypes of human mesenchymal cells in vitro … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(32 citation statements)
references
References 72 publications
(87 reference statements)
4
28
0
Order By: Relevance
“…It has been reported that activation of ITGA5 induced both IGF2 and IGFBP2 expressions via FAK, ERK1/2, and PI3K signaling, which resulted in osteogenic differentiation in hMSCs [ 53 ]. In another study, cilengitide (a cyclic RGD pentapeptide) is an ITGAV inhibitor [ 54 ] that can abolish ossification in BM-MSCs [ 55 ]. The interaction between osteopontin and integrin αv/β1 induced osteogenesis and inhibited adipogenesis in MSCs [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that activation of ITGA5 induced both IGF2 and IGFBP2 expressions via FAK, ERK1/2, and PI3K signaling, which resulted in osteogenic differentiation in hMSCs [ 53 ]. In another study, cilengitide (a cyclic RGD pentapeptide) is an ITGAV inhibitor [ 54 ] that can abolish ossification in BM-MSCs [ 55 ]. The interaction between osteopontin and integrin αv/β1 induced osteogenesis and inhibited adipogenesis in MSCs [ 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Integrin subunit alpha V (ITGAV), a member of the integrin family, has been found to be associated with cell differentiation and metastasis and can serve as a prognostic biomarker for a variety of cancers [29][30][31]. In our study, we found that ITGAV mRNA expression was significantly upregulated in CCA and that upregulated expression was associated with better prognosis in CCA patients through bioinformatics analysis.…”
Section: Discussionmentioning
confidence: 61%
“…Previous work shows that DP cells, but not PFi, will readily differentiate down an osteogenic lineage in vitro [13], however it is not known if this is due to baseline differences in the epigenetic landscape between each cell type. To ascertain the baseline landscape, and determine if DP are pre-sensitised to differentiate down an osteogenic lineage in vitro, we assessed both the chromatin accessibility and transcriptional profiles of each cell type in GM, ATAC-seq and RNA-seq libraries were generated from DP and PFi cells grown in GM, with DNA and RNA isolated hours after cell seeding.…”
Section: Pfi and Dp Cells Share Similar Chromatin Organisation In Gm Conditionsmentioning
confidence: 95%
“…Lineage tracing studies have revealed that a fibroblast subtype found in the hair follicle, dermal papilla (DP) fibroblasts, share a common developmental progenitor with an interfollicular subtype, papillary fibroblasts (PFi) [9]. Despite arising from the same developmental progenitor [9], DP and PFi have distinct identities both in vivo and in vitro; DP cells can differentiate down osteogenic [10,11] and adipogenic [11,12] linages in vitro, while PFi lack this differentiation capacity [13]. DP and PFi also differ in their response to mechanical stimuli, and we previously demonstrated that mechanical stimulation of cells in culture (in the form of a single 165 kPa shock wave (SW) in air) in combination with osteogenic media (OM), resulted in enhanced and accelerated osteogenic differentiation of DP, whereas PFi were unresponsive to this stimuli [13].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation